1955
DOI: 10.1021/jo01122a001
|View full text |Cite
|
Sign up to set email alerts
|

The Isopropyl Cresols

Abstract: The Friedel-Crafts reaction has been found to be well adapted to the synthesis of thymol (1). For this preparation m-cresol is alkylated with isopropyl chloride in the presence of aluminum chloride, using ethylene dichloride as solvent. When this procedure was applied to o-cresol there was obtained in good yield a product which, after crystallization, melted sharply at 36-36.5°. This material, which will be referred to as pseudo-carvacrol, gave several derivatives melting correctly for those of carvacrol; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1959
1959
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…Similar isomerization processes also took place with more complex substrates, such as carvone (Scheme 1). Under standard hydrogenation conditions, complex 4 b induced a double-bond isomerization to yield 5-isopropyl-2-methylphenol [19] without further reaction.…”
Section: Substrate Screeningmentioning
confidence: 99%
“…Similar isomerization processes also took place with more complex substrates, such as carvone (Scheme 1). Under standard hydrogenation conditions, complex 4 b induced a double-bond isomerization to yield 5-isopropyl-2-methylphenol [19] without further reaction.…”
Section: Substrate Screeningmentioning
confidence: 99%
“…1). Therefore, the MeOH fraction was further separated on a silica gel column eluted with stepwise gradients of nhexane-EtOAc and then purified by HPLC to give compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) as shown in Fig. 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Two new compounds (1, 2) and seventeen known compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) were isolated from the leaves of B. dracunculifolia and the chemical structures were determined by spectroscopic means. Cytotoxicity testing of the compounds isolated in this study revealed the monoterpene phenols like compounds 4, 6, and 17 (dimer) and the sesquiterpene alcohols such as compounds 8, 10, 11, 13, and 16 exhibited strong cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The small amount of vic-thymol and the improvement in rate of sym-thymol can be explained by the thermal stability of the mono-alkylated cresol in the presence of acid catalyst, the order being as follows: sym-thymol > thymol > p-thymol > vic-thymol. 24 Sym-thymol is the thermodynamically favoured isomer as it has higher stability compared to the other isomers. This increased stability arises from the fact that the inductive effect of the propyl and methyl groups in the meta-positions does not prevent delocalisation of the lone pair electrons on the hydroxyl group into the aromatic system to the same extent as would be the case for these substituents in the para and ortho-positions.…”
Section: The Effect Of Reaction Timementioning
confidence: 99%